Do Foreign Portfolio Investment Flows Affect Financial Asset Prices? Evidence From Malaysia - Karuppiah, Manimakudom (2017)
The debate regarding usefulness of Foreign Portfolio Investment (FPI) and its impact on the prices of financial assets including stocks, bonds and exchange rates is inconclusive. There is mixed evidence of its effectiveness for host economy and this study intends to explore this issue for Malaysian economy for the period 2007-2015. We have used Ordinary Least Square approach due to the suitability with research objectives and since the data fulfills the underlying assumptions of this technique. It has been observed that Equity markets have positive and significant relationship with FPI and Gross Domestic Product (GDP) while negative and significant relationship with inflation. Similarly, exchange rates have negative and significant relationship with FPI, GDP and inflation. Lastly, interest rates have negative and significant relationship with FPI and positive and significant relationship with GDP and inflation. The results are found valid and robust for all the three models. This study is useful for regulators as it will help them in understanding the consequences of FPI for the financial sector. It is hoped that individual as well institutional investors would also benefit from this work as it will increase their knowledge of financial markets and investment environment.